2021
DOI: 10.3389/fcimb.2021.671109
|View full text |Cite
|
Sign up to set email alerts
|

Combining Metagenomic Sequencing With Whole Exome Sequencing to Optimize Clinical Strategies in Neonates With a Suspected Central Nervous System Infection

Abstract: ObjectivesCentral nervous system (CNS) infection has a high incidence and mortality in neonates, but conventional tests are time-consuming and have a low sensitivity. Some rare genetic diseases may have some similar clinical manifestations as CNS infection. Therefore, we aimed to evaluate the performance of metagenomic next-generation sequencing (mNGS) in diagnosing neonatal CNS infection and to explore the etiology of neonatal suspected CNS infection by combining mNGS with whole exome sequencing (WES).Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Metagenomic next-generation sequencing (mNGS) is an unbiased method that can theoretically detect all pathogens in clinical samples, and is especially suitable for the detection of complex, rare, novel, and atypical infectious diseases (Ge et al, 2021, Jin Wenting et al, 2020. Especially for some RNA viruses, mNGS may be the only feasible method of detection (Babiker et al, 2020, van Boheemen et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomic next-generation sequencing (mNGS) is an unbiased method that can theoretically detect all pathogens in clinical samples, and is especially suitable for the detection of complex, rare, novel, and atypical infectious diseases (Ge et al, 2021, Jin Wenting et al, 2020. Especially for some RNA viruses, mNGS may be the only feasible method of detection (Babiker et al, 2020, van Boheemen et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Of which, four studies were retrospective ( 15 , 16 , 18 , 20 ) and eight were prospective ( 9 , 17 , 19 , 21 25 ). Studies were conducted in the following countries: China ( 9 , 17 , 22 , 23 ), the United States ( 16 , 18 21 , 24 ), Canada ( 15 ), and the unknown ( 25 ). A total of 1,249 participants were analyzed in the 12 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The 12 included studies were published between 2017 and 2021. Of which, four studies were retrospective (15,16,18,20) and eight were prospective (9,17,19,(21)(22)(23)(24)(25). Studies were conducted in the following countries: China (9,17,22,23), the United States (16, 18-21, 24), Canada (15), and the unknown (25).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an efficient and accurate method to identify such pathogens in complex infections would be very important and helpful for clinical practice. Ge et al 21 studied 88 neonates with a suspected central nervous system infection and showed that mNGS had a higher positivity rate than conventional methods. Among the 101 CSF samples collected, 20 (19.8%) showed a positive result by mNGS, whereas the pathogen could only be detected in 5 (4.95%) samples by conventional methods.…”
Section: Application Of Mngs In Complex Infectionsmentioning
confidence: 99%